Differentiating middle school students’ conceptions of engineering from interests in engineering - Schilling, Malle R.; Matusovich, Holly M.; Grohs, Jacob R.; Paradise, Tawni; Carrico, Cheryl (Frontiers in Education, 2025)
IntroductionDeveloping and deploying research tools that measure pre-college students’ conceptions of engineering is challenging, and often surveys relying on measurements of interest and identity are used to understand students’ goals related to engineering. The purpose of this study is to describe the creation of and preliminary findings from a survey in the context of long-term engagement with middle school students.MethodsTo identify underlying factors related to student conceptions of engineering, this study leveraged exploratory factor analysis (EFA) with survey data from 360 middle school students along with descriptive and inferential statistics to understand more about the relationship between conceptions and interest and identity.ResultsResults from the EFA revealed a total of five factors related to a range of students’ conceptions of engineering and interest and identity for engineering. Descriptive and inferential statistics further iterated that conceptions of engineering are distinct from interest and identity, meaning that, in some instances, understanding what engineering is does not always lead to increased interest.DiscussionThis study emphasizes the need to differentiate discussions about interest and identity in engineering from conceptions of engineering through more nuanced analysis of data. This study also contributes promising survey items and measures that can be translated to different contexts and further explored to measure conceptions of engineering.